The Effectiveness of Coaching Prisoners With The Therapeutic Community Method in The Cirebon Class IIA Narcotics Penitentiary - Hamja Hamja; Lukman Nul Hakim; Murtiningsih Kartini (Faculty of Law, Universitas Jenderal Soedirman, 2022)
Drug abuse is a significant problem, various rehabilitation efforts are carried out at the Cirebon Class IIA Narcotics Penitentiary, one of which is by using therapeutic communities to provide expectations of drug abuse inmates. The problems studied in this research are related to the rehabilitation of prisoners and their implications with the therapeutic community method at the Cirebon Class IIA Penitentiary. This research is empirical research that uses survey methods, observations, interviews, and literature studies. The data obtained are collected and analyzed qualitatively by analytical descriptive methods. The results showed that the therapeutic community can be implemented optimally but is still faced with the first problem therapeutic community has not been focused on the fundamentals of the resident's addiction and the second problem is that the resident is still faced with having to fight his mind with the effects of the relapse he feels.Keywords: Coaching, Therapeutic community, Relapse.